Assessment of hypertension management in primary health care settings in Kinshasa, Democratic Republic of Congo. Issue 1 (June 2015) - Lulebo, Aimée; Mapatano, Mala; Kayembe, Patrick; Mafuta, Eric; Mutombo, Paulin; Coppieters, Yves
Abstract Background Hypertension-related complications have become more diagnosed at secondary and tertiary care levels, in the Democratic Republic of the Congo (DRC), probably indicative of poor management of hypertensive patients at primary health care level. This study aimed to assess the management of hypertension in primary health care settings by using guidelines of the International Forum for Prevention and Control of HTN in Africa (IFHA). Methods A multi-center cross-sectional study was carried out in primary health care settings. A total of 102 nurses were surveyed using a structured interview. Mean and proportion comparisons were performed using thet Student test and the Chi-square test respectively. The Kinshasa Primary Health Care network facilities were compared with non-Kinshasa Primary Health Care network facilities. Results From the 102 nurses surveyed; 52.9 % were female with a mean age of 41.1, (SD = 10) years, merely 9.5 % benefited from in-job training on cardiovascular diseases or their risk factors, and 51.7 % had guidelines on the management of hypertension. Less than a quarter of the nurses knew the cut-off values of hypertension, diabetes and obesity. Merely 14.7 % knew the therapeutic goals for uncomplicated hypertension. Several of the indicators for immediate referral recommended by IFHA were unmentioned. The content of patient education was lacking, avoiding stress being the best advice provided to hypertensive patients. The antihypertensive most used were unlikely to be recommended by the IFHA. Conclusions This study showed a considerable gap of knowledge and practices in the management of hypertensive patients at primary health care facilities in Kinshasa pertaining to the IFHA guidelines. We think that task-shifting for management of hypertension is feasible if appropriate guidelines are provided and nurses trained.